Gérer la pénurie, produire du commun - Claude Le Gouill; Franck Poupeau (Revue de la Régulation)
This survey explores the relationships between small local organizations and socio-technical systems based on large state or private infrastructures. Its purpose is to transform water cooperatives in the expanding peripheries of the city of La Paz in Bolivia. Its objective is to determine under what conditions a cooperative can produce the common through an analysis of the social conditions of self-organization. To this end, this article develops a sociological perspective that is not limited to the analysis of the urban network or the institutional dimension of the operator, but reintroduces variables in terms of specific skills, knowledge and know-how linked to each type of organization, in order to take into account the social characteristics of the groups concerned and the degree of interpenetration between local systems, urban networks and socio-environmental inequalities.